ADAKAH PERUBAHAN KONSENTRASI SPASIAL INDUSTRI MANUFAKTUR DI INDONESIA, 1976-2001? - Kuncoro, Mudrajad (Journal of Indonesian Economy and Business, 2004)
Although a number of economists and business strategists have recently become moreinterested in spatial analysis, very few has examined the phenomena of regional clustering in Indonesia using regional data. This paper explores to what extent the unequal geographic distribution of manufacturing activities in Indonesia has persisted or changed over time. The Theilâs entropy index is proved useful to highlight the uneven geographic distribution in Indonesia. First, we find that Indonesia constitutes an extreme case of geographic concentration. Second, the entropy between islands has played a prominent role in explaining the spatial inequality across provinces in Indonesia. Third, the pattern of spatial inequality formed a âUâ curve suggesting a period of dispersing manufacturing activity has been replaced by a period of increasing geographic concentration. Fourth, the Chow tests confirm that structural change has occurred from 1985 onwards. Our findings challenge the general consensus in the new economic geography that trade liberalization encourages dispersing manufacturing activity.Key words: geographic concentration, Theilâs entropy, structural shift, trade liberalization.